2008
DOI: 10.1007/s00270-008-9449-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Evaluation of Carotid Artery Grafting with Prefabricated Small-Diameter, Small-Intestinal Submucosa Grafts in Sheep

Abstract: The purpose of this study was to report the longitudinal angiographic evaluation of prefabricated lyophilized small-intestinal submucosa (SIS) grafts placed in ovine carotid arteries and to demonstrate a variety of complications that developed. A total of 24 grafts, 10 cm long and 6 mm in diameter, were placed surgically as interposition grafts. Graft patency at 1 week was evaluated by Doppler ultrasound, and angiography was used for follow-up at 1 month and at 3 to 4 months. A 90% patency rate was found at 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…However, long-term implantation of cell-free SIS conduits in the arterial circulation showed aneurysm formation and vascular expansions possibly due to thrombosis and matrix degradation [Pavcnik et al, 2009]. Our experiments showed significant platelet attachment on the surface of cell-free SIS within minutes even after treatment with a clinical dose of heparin and warfarin sodium, suggesting that endothelialization is necessary for the development of implantable vascular grafts.…”
Section: Discussionmentioning
confidence: 61%
“…However, long-term implantation of cell-free SIS conduits in the arterial circulation showed aneurysm formation and vascular expansions possibly due to thrombosis and matrix degradation [Pavcnik et al, 2009]. Our experiments showed significant platelet attachment on the surface of cell-free SIS within minutes even after treatment with a clinical dose of heparin and warfarin sodium, suggesting that endothelialization is necessary for the development of implantable vascular grafts.…”
Section: Discussionmentioning
confidence: 61%
“…In vascular tissue engineering, this paracrine signaling appears to be an important mechanism [18][19][20][21][22] by which tissueengineered blood vessels (TEBVs) remodel. Recent studies have shown they possess a dynamic environment that is repopulated with host cells, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] such as by the inward migration of vascular smooth muscle cells (SMCs).…”
Section: Introductionmentioning
confidence: 99%
“…SIS from swine displays very low immunogenicity without provoking immune-mediated inflammatory reactions when transplanted. To date, SIS has been extensively used as scaffolds for tissue engineering applications of artery [7], bladder [8], intestinal tract [9,10], and tendon [11]. The US FDA has approved its use in human for urogenital procedures, such as hernia repair, cystoplasties, ureteral reconstructions, stress incontinence, peyronie's disease, penile chordee, even urethral reconstruction for hypospadias and strictures [12e16].…”
Section: Introductionmentioning
confidence: 99%